What to do about unprotected strikes at Nkomati Mine? - Phakathi, Nkosana Christian (Department of Commercial Law, 2021)
Background and motivation: Nkomati Joint Venture Mine (Nkomati) is situated in Mpumalanga between the towns of Machadodorp, Barberton and Nelspruit. It is a mining company, mining a variety of minerals, however their primary mineral is Nickel. It employs around 494 employees. The author, continuously observed that employees, often ignore grievance procedures when dissatisfied and embark on unprotected strikes, that is strikes that do not comply with section 64 and 65 of the Labour Relations Act 66 of 1995 (the LRA)1 . This ignorance often result in relationship discomfort, complaints, grievances, disciplinary action and other forms of workplace conflict that have a negative impact on organisational functioning. The author subsequently intends to analyse unprotected strikes at Nkomati in order to identify problem areas and recommendations to eliminate, manage and/or reduce such actions. The author believes that unprotected strikes may be reduced, managed and/or eliminated if parties are aware of the position of labour law on unprotected strikes including violence, damaging of property and intimidation during strikes. These unawareness could be significant contributor to final warnings issued to all employees who participated in the unprotected strike and 11 employees who were dismissed for misconduct during the said unprotected strike on 23 April 2018 at Nkomati. A better understanding on how employees must conduct themselves during strikes may promote the quality of employment relations at Nkomati. Problem statement and purpose The right of employees to strike is entrenched in the Constitution of the Republic of South Africa in terms of section 23(2)(c). It is important to note that the right may nonetheless be limited as encapsulated in section 36 of the constitution.2 The primary objective for employees to embark into to a strike action is to inflict economic harm on their employers so that the employer will accede to their demands.3 The abuse of such power by trade union or employees has become rather a thorny issue for employers.4 The main purpose of this study is to analyze in depth the legal implications of employees' participation in unprotected strikes. The study will cover the following discussions: Chapter 1 gives the introduction and background. Chapter 2 deals with the legal framework. Chapter 3 deals with remedies. Lastly, Chapter 4 draws conclusions and makes recommendations. The study will also determine if Schedule 8 of the Code of Good Practice: Dismissal, according to item 6(2), is effective in deterring unprotected strikes and unlawful conduct during strikes. The study examines the Nkomati disciplinary code and procedure mechanisms to curb unprotected strikes that are marred with unlawful conduct. The amount of unprotected and violent strikes, while the Nkomati events provide an example of one situation. The study will determine if there are any areas of the law or other alternative mechanisms that can be developed to curb the occurrence of unprotected strikes associated with unlawful conduct. Research questions: This research seeks to answer these questions: i. What is an unprotected strike and what are the legal implications of participating in such a strike? ii. What legal mechanisms can be used to deal with unprotected strikes? iii. How should misconduct during strikes be dealt with? iv. Does Schedule 8 to the LRA, the Code of Good Practice: dismissal, offer meaningful ways to curb unprotected strikes and unlawful conduct? Finally, the analysis of the consequences of unprotected strikes assists the study to determine methods through which proactive approaches can be developed in order to minimize or deter unprotected strikes and unlawful conduct during strikes with the objective of improving relations between employees and Nkomati.7 The study recommends pragmatic suggestions to both employees and Nkomati management to harmoniously resolve their disputes and grievances. Research methodology: The dissertation comprises of desktop research. Information will be drawn from documented evidence which is empirical in nature. Furthermore, the dissertation will entail the analysis of legislation, case law, journals and articles. A comparison will be made on the applicable laws in South Africa and what had transpired at Nkomati with the aim to identify any gaps in our labour laws governing unprotected strikes. In order to paint a clear picture of some experiences, the author of the dissertation will discuss relevant Nkomati events pertaining to the strike and will provide an analysis on them. Reference is made to the Constitution, as the primary source of the right to strike. The dissertation refers extensively to the Labour Relations Act (LRA), as the statute which makes provision for the right to strike, and other provisions relating to strikes. Dissertation structure: Chapter 1 deals with the introduction and background. Chapter 2 deals with the legal framework. Chapter 3 deals with remedies for unprotected strikes and unlawful activities during strikes. Lastly Chapter 4 deals with conclusion and recommendations.